Epigallocatechin-3-Gallate Activates Nrf-2, NF-?B and TNF-? Protein Signaling Pathways in Rat Muscle Tissue Damage - Yüksek, Rumeysa Demiroğlu; Erman, Fazilet; Beyaz, Seda; Gök, Özlem; Erman, Orhan; Özercan, İbrahim Hanifi; Aslan, Abdullah (Inst Tecnologia Parana, 2026)
Cisplatin, used as an effective drug in cancer patients, has become a popular topic in studies conducted in recent years. It is known that cisplatin terminates the vital activities of healthy cells as well as cancer cells. Epigallocatechin-3-gallate (EGCG), a member of the catechin group, is a natural antioxidant known to promote and improve health. Catechins, due to their regulatory effect on apoptosis and autophagy, have attracted increasing interest in their positive health effects on various diseases. This study aims to investigate the effect of EGCG on Nrf-2, NF-kappa B, and TNF-alpha protein signaling pathways against muscle tissue damage caused by cisplatin. A total of 28 male rats were used in the study, creating 4 groups. The experimental period was 28 days (4 weeks). The protective and healing effects of EGCG against cisplatininduced damage in muscle tissue were investigated. Catalase (CAT) activity, malonaldehyde (MDA), and glutathione (GSH) levels were measured in a spectrophotometer. Expression levels of Nrf-2, NF-kappa B, and TNF-alpha proteins were determined using the Western blot method. When compared to the cisplatinadministered group, MDA levels decreased in the EGCG+Cisplatin-administered group, while CAT activity and GSH levels increased. It was found that EGCG used for therapeutic purposes reduced the expression of Nrf-2, NF-kappa B, and TNF-alpha proteins. Histopathological examination showed that muscle tissue damage occurred in the cisplatin group, while the damage decreased in the EGCG+Cisplatin-administered group. Our findings show that EGCG can prevent toxicity due to its anti-inflammatory effect against tissue damage caused by cisplatin.
Keywords: EGCG; Nrf-2; MDA; Muscle; TNF-alpha